2001
DOI: 10.1002/jnr.10064
|View full text |Cite
|
Sign up to set email alerts
|

Role of specific aminotransferases in de novo glutamate synthesis and redox shuttling in the retina

Abstract: In this study aminotransferase inhibitors were used to determine the relative importance of different aminotransferases in providing nitrogen for de novo glutamate synthesis in the retina. Aminooxyacetate, which inhibits all aminotransferases, blocked de novo glutamate synthesis from H(14)CO(3)(-) by more than 60%. Inhibition of neuronal cytosolic branched chain amino acid transamination by gabapentin or branched chain amino acid transport by the L-system substrate analog, 2-amino-bicyclo-(2,2,1)-heptane-2-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
72
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 40 publications
3
72
0
Order By: Relevance
“…In the retina, Ͼ60% of glutamate de novo synthesis depends on transaminases such as alanine transaminase, aspartate transaminase, and branched amino acids transaminase (49). However, only aspartate and not alanine or branched amino acids increase with Zaprinast.…”
Section: The Effect Of Zaprinast On Glutamate and Aspartate Occurs Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In the retina, Ͼ60% of glutamate de novo synthesis depends on transaminases such as alanine transaminase, aspartate transaminase, and branched amino acids transaminase (49). However, only aspartate and not alanine or branched amino acids increase with Zaprinast.…”
Section: The Effect Of Zaprinast On Glutamate and Aspartate Occurs Inmentioning
confidence: 99%
“…Glutamate may also decarboxylate into GABA, but Zaprinast does not increase GABA content in the retina. Therefore, the amino group of aspartate most likely comes from glutamate transamination (49).…”
Section: The Effect Of Zaprinast On Glutamate and Aspartate Occurs Inmentioning
confidence: 99%
“…Moreover, it was shown that when mosquitoes or dissected tissues are exposed to an ammonia challenge in vivo or in vitro, ALAT plays an important role in both mosquito whole body (4,6) and tissues (8) contributing to the homeostasis of amino acid metabolism. Recent studies indicate that administration of high doses of L-cycloserine, a well-characterized inhibitor of ALAT (12)(13)(14)(15)(16), affects blood-fed mosquito survival and motor activity, suggesting an interference with ammonia and carbohydrate metabolism in a time-dependent manner (17). To compare this finding, we reduced A. aegypti ALAT through RNAi gene silencing and examined the outcome of blood-fed female mosquitoes injected with double-stranded RNA (dsRNA) against ALAT.…”
mentioning
confidence: 99%
“…Indeed, aminooxyacetic acid inhibits insulin secretion stimulated by glucose and other nutrients (18,22). All of the available inhibitors of BCATm preferentially block other transaminases (23)(24)(25). In this study, we used BCATm Ϫ/Ϫ mice to determine the precise role of this enzyme in KICSIS and LSIS, therefore resolving the catabolism versus transamination dispute that has lasted for more than 30 years.…”
mentioning
confidence: 99%